The library for the incarcerated male juveniles: An observation of five correctional schools - Rafedzi, E.R.K.; Abrizah, Abdullah (2014)
This qualitative study extends our earlier research on what we have learned so far about the information needs of Malaysian male juvenile offenders. This focus is important to consider when designing and delivering the best possible library services to this group. The study explores the extent the prison library is used as the environment for information seeking of male juvenile delinquents. Data were collected using participants observation with 27 juveniles (13 to 21 years old) living in five correctional schools in Malaysia. Our observation at all research sites has led us to conclude that the prison library does not play that much roles in addressing the participants' information needs. Current findings add to the limited literature on juvenile offenders' information needs and how the prison libraries meet the needs of this people.